Development and study of Molten salt electrode position system using different voltage feeding - Miron Gakim (2018)
Electrochemical conversion of CO2 into solid carbon is one of the conversion techniques that had been developed which contributes in the carbon capture and utilisation (CCU). The electro reduction process in molten alkali/earth alkali carbonate salt reduces carbonate ion to form solid carbon and alkali/earth alkali metal oxide. Then, the metal oxide reacts with CO2 to reform carbonate ion. This cycle is called the fixation process. However, at a low operating temperature, the charge transfer of the electrolysis process was low and experience current drop after the operation period was prolonged. These leads to the low production rate of solid carbon. The factor that caused the low charge transfer has been described in this thesis. The motivation of study is to improve the charge transfer at operating temperature range 550 - 570 °C and driven at constant voltage 4V which was previously claimed could promotes high current efficiency at this temperature. Therefore, the main objective was to instigate an experimental understanding of electrolysis process on carbon electrodeposition under different voltage feeding. The voltage feeder was invented as to provide electrochemical agitation in the electrolysis system. The electrolysis system with Double Pole Double (DPDT) switch was developed in the electrolysis system as the voltage feeder. The agitation was done by changing the DC current flow manually to drive the electrolysis process. The gated pulse and alternate voltage feeding operation was described in this thesis. The effect of the voltage feeding on electrolysis in molten Li2CO3- Na2CO-3 K2CO3 with mole ratio (0.44: 0.30:0 .26) and salt mixture CaCO3- Li2CO3- LiCI with mole ratio (0.09: 0.28:0 .63) was studied. The effect of voltage feeding on total charge transfer and carbon yield was studied. The succeed edelector deposited products were characterized through EA,S EM-EDXT, EM, XRD and ATR-FTIR. The results showed the total charge transfer under alternate voltage feeding was extremely high compared to gated pulse and continuous voltage feeding which leads to high carbon deposition rate. Through EA characterisation, it was found that the produced sample under different voltage feeding exhibit higher than 60% of carbon content, therefore the deposited samples were carbon dominant. However, approximately 12% of carbon content was observed for samples produced in Li2CO3- Na2CO3- K2CO3 under alternate voltage feeding. Under the SEM-EDX analysis, the observed essential carbon structure was found differed based on the types of the salt bath and also effected with voltage feeder. Carbon nanotubes structure was seen in the samples prepared under alternate voltage feeding for both salt mixtures. TEM analysis confirmed the existence of carbon nanotubes. Through XRD analysis, the obtained dominant carbon deposition was amorphous type. Due to the corrosion of the electrode, crystallite of metallic compound was significantly observed for sample prepared using alternate voltage feeding in molten mixture Li2CO3- Na2CO3- K2CO3T. he functional group on the surface of the sample was hard to determined due to the noise from the strong IR spectra of intrinsic diamond peak from the FIR probe at region 1700 - 2700 cm-1. In alternate voltage feeding, the charge transfer in the process was high, however the carbon yield was relatively low. Henceforth, it leads to low current efficiency, and therefore high energy density was necessary to produce carbon. It was found that with the increased of carbon loses during the process, it reduced the current efficiency and thus increased the energy consumption.